Cultural influences on crisis communication strategies in Nigeria - Aruku, Kalita Joseph; Ikangkang , Joseph; Utsu, Charles Ushie; Emuru, Linus Ejunka (Yayasan Mitra Persada Nusantara, 2025)
In an era characterized by globalization and rapid information exchange, the role of cultural influences in crisis communication strategies has become increasingly significant. This study explores the unique cultural dynamics that shape crisis communication in Nigeria, a nation marked by its rich diversity and complex socio-political landscape. Employing a case study analysis methodology, this research integrates three theoretical frameworks: Cultural Dimension Theory, Situational Crisis Communication Theory, and Social Identity Theory. These theories provide a robust foundation for understanding how cultural factors affect communication during crises and the perception of organizations by various stakeholders. Through an examination of key case studies within the Nigerian context, the findings reveal that cultural dimensions such as collectivism, power distance, and uncertainty avoidance significantly influence the efficacy of crisis communication strategies. Furthermore, the study highlights the importance of aligning communication practices with cultural expectations to foster trust and facilitate effective engagement with diverse audiences. This research contributes to the broader field of crisis communication by elucidating the intersection of culture and communication strategies, offering valuable insights for practitioners in Nigeria and beyond. By implementing these recommendations, organizations in Nigeria can enhance their crisis communication strategies, fostering greater trust and resilience in the face of adversity. Understanding and integrating cultural influences into crisis communication not only strengthens organizational reputation but also contributes to social cohesion and community well-being during challenging times.